I papiri di Eschilo e di Sofocle Atti del convegno internazionale di studi. Firenze, 14-15 giugno 2012 - Casanova, Angelo Alfredo; BASTIANINI, Guido (Edizioni dell'Istituto Papirologico «G. Vitelli», 2013)
The volume contains the transcription of the reports presented at the International Conference held in Florence on 14th and 15th June 2012: there are 15 original essays, written (upon request) by authoritative scholars of various Italian and foreign universities, on the important contributions made by their papyrus finds over more than a century to the knowledge of the lost works by Aeschylus and Sophocles, as well as on the value of the papyri for the constitution of the text of their preserved tragedies. The essays are equally divided between Aeschylus and Sophocles, and touch on all the major questions which the study of papyrology has raised for the philological and literary research on the two great tragedy writers. Both for the prestige of the authors and for the variety of the topics addressed, the volume offers an interesting and authoritative picture of the 'state of the art' of the studies in this regard, in light of the interrelationships between papyrology and Greek literature.